Alpha‐blockers for treating neurogenic lower urinary tract dysfunction in patients with multiple sclerosis: A systematic review and meta‐analysis. A report from the Neuro‐Urology Promotion Committee of the International Continence Society (ICS). Issue 6 (16th May 2019) - Schneider, Marc P.; Tornic, Jure; Sýkora, Radek; Abo Youssef, Nadim; Mordasini, Livio; Krhut, Jan; Chartier‐Kastler, Emmanuel; Davies, Melissa; Gajewski, Jerzy; Schurch, Brigitte; Bachmann, Lucas M.; Kessler, Thomas M.
Abstract: Aim: We aimed to systematically assess the evidence on the efficacy and safety of alpha‐blockers in patients with multiple sclerosis (MS) suffering from neurogenic lower urinary tract dysfunction (NLUTD). Methods: The Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) statement was used to perform this systematic review. An electronic search of Cochrane register, Embase, Medline, Scopus (last search 3 March 2018) and screening of reference lists as well as reviews were used to identify the studies. Articles were included if they reported on efficacy/safety of alpha‐blockers for the treatment of NLUTD in patients with MS. Results: After screening of 7′015 abstracts, three studies enrolling a total of 50 patients were included: one randomized, placebo‐controlled, single‐blind trial and two prospective cohort studies. Alpha‐blocker treatment was successful in 50% to 96% of the patients. Pooling data from the three included studies, the relative risk for successful alpha‐blocker treatment was 3.89 (95% confidence interval 2.7‐7.0). The general safety profile of alpha‐blockers was favorable with 8% of the patients reporting adverse events. Conclusions: Alpha‐blockers may be effective and safe for treating NLUTD in female and male patients with MS but the studies were small and the overall quality of evidence was low. To make definitive conclusions, well designed randomized controlled trials are highly warranted.